PERGERAKAN LUTUNG JAWA Trachypithecus auratus (E. Geoffroy 1812) PADA FRAGMEN HABITAT TERISOLASI DI TAMAN WISATA ALAM GUNUNG PANCAR (TWAGP) BOGOR [The Movement of Javan Langur Trachypithecus auratus (E. Geoffroy 1812) in Isolated Habitat Fragment in TWAGP Bogor] - Sulistyadi, Eko; Kartono, Agus Priyono; Maryanto, Ibnu (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Javan langur is protected spesies of primates that highly threatened. Habitat degradation as a major threat causes javan langur Trachypithecus auratus (E. Geoffroy 1812) populations living in isolated habitat fragments. The research was carried out to determine the daily movement of javan langur in TWAGP as form of adaptation in isolated habitat fragments. The study was conducted in May-June 2012 by using focal animal sampling method. Vegetation analysis was performed with a point centered quarter method. The results showed that there were three major land cover types used by the Javan langur, i.e. forest, transitional forest-cultivation and cultivation. The dominant activity occurred in transisional forest-cultivation habitat (48.19%). The highest proportion of activity wass resting (33.65%) followed by feeding (30.68%), moving (27.08%) and social activities (8.60%). Based on the variations of vegetation strata, the dominant activity performed at stratum C(4-20 meters) accounted for 80.07%.